An experimental study on the thermal radiation attenuation effect of water mist from flat fan nozzle. (1st March 2023) - Zhou, Liang; Shi, Xuanshuo; Jiang, Huiling; Xu, Zhicheng; Li, Songzhi; Xu, Wenjie
Highlights: Influencing factors on attenuation effect of water mist were systematically studied. Three vertical zones are identified based on the attenuation characteristics. The attenuation rate decreases linearly with temperature at different pressures. An exponential correlation is found between attenuation rate and mist thickness. The increase in attenuation with rising pressure and mist thickness becomes smaller. Abstract: The factors which influence the radiation attenuation efficiency of the water mist from flat fan nozzle have been investigated in the study. The characteristic parameters of the water mist were obtained by laser-based diagnostic system for flow field. Both blackbody furnace and gasoline pool fires were used as heat sources in the experiments. The influences of system pressure, the vertical distance from the nozzle, the temperature of the radiation source and the number of the mist layers on the radiation attenuation effectiveness have been systematically studied. The experimental results showed that when the vertical distance down the nozzle increased from 20 cm to 200 cm, the radiation attenuation efficiency increased at first, then remained almost stable for a substantial distance and decreased afterwards, and three vertical zones were identified based on the attenuation characteristics; as the temperature of the blackbody furnace radiation aperture increased from 1000 °C to 1300 °C, the radiation attenuation efficiency had a certain decrease, a linear correlation was found between the mitigation rate and the radiative source temperature under different system pressures. The attenuation effectiveness improved with the increase of both system pressure and the number (thickness) of water mist layer, while the augmentation rate in attenuation slowed as the system pressure and the water mist thickness increased. The findings provide useful insights into the optimization of attenuation performance of water mist and potentially contribute to the protection against thermal radiation in fields like the fluorine chemical industry.